2006
DOI: 10.3171/spi.2006.4.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Chimney sublaminar decompression for degenerative lumbar spinal stenosis

Abstract: Object The authors evaluated the efficacy and safety of so-called chimney sublaminar decompression, a new technique to decompress the degenerative stenotic lumbar spinal canal without stripping of the paravertebral muscles. Methods Eighteen patients (nine men and nine women whose mean age was 67 years) with symptoms of claudication were selected to undergo chimney sublaminar decompression. The duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…This could probably be because of an anatomically wider canal at L5-S1, thus placing the lateral recesses farther wide apart (also corroborated by higher mean preoperativeinterfacet distance at L5-S1 despite a comparable AP diameter, lateral recess depth and lateral recess angle to other stenosed levels in this series), thus hindering adequate visualisation and limiting the extent of decompression possible through a split spinous approach. As has been previously published, 10,11,24 we believe that effective lateral recess decompression can be obtained by proper retraction of the paraspinal muscles, changing the lateral tilt of the operating table, and approaching the side of decompression from the contralateral side viewing obliquely under the split lamina and paraspinal muscles. Though, this procedure is not effective for treating foraminal stenosis as noted by the radiologic values in our series, foraminal dissection and freeing of the adhesions around the nerve root in the foraminal area may be responsible for the clinical benefit seen.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This could probably be because of an anatomically wider canal at L5-S1, thus placing the lateral recesses farther wide apart (also corroborated by higher mean preoperativeinterfacet distance at L5-S1 despite a comparable AP diameter, lateral recess depth and lateral recess angle to other stenosed levels in this series), thus hindering adequate visualisation and limiting the extent of decompression possible through a split spinous approach. As has been previously published, 10,11,24 we believe that effective lateral recess decompression can be obtained by proper retraction of the paraspinal muscles, changing the lateral tilt of the operating table, and approaching the side of decompression from the contralateral side viewing obliquely under the split lamina and paraspinal muscles. Though, this procedure is not effective for treating foraminal stenosis as noted by the radiologic values in our series, foraminal dissection and freeing of the adhesions around the nerve root in the foraminal area may be responsible for the clinical benefit seen.…”
Section: Discussionmentioning
confidence: 71%
“…Watanabe et al 10 improvised this technique by splitting the spinous process, preserving bilateral paraspinal muscle integrity and performing a complete laminectomy. Lin et al 24 reported a slight modification wherein they preserved the outer one third thickness of the lamina, bent it laterally using an osteotome along with the overlying paraspinal muscles and removed the inner two thirds thickness of the lamina. They minimised paraspinal muscle injury further by preserving their attachment to the laminar surface which was elevated in the original SPSL technique.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of the studies were conducted prospectively 1,5-8, 15,16,21,32,33,35,37,46,47,52 and 9 were conducted retrospectively. 10,14,19,20,27,[38][39][40][41] Postoperative instability was defined variably across studies, including increase in sagittal translation between flexion-extension radiographs by 2 mm, 1,8,14 3 mm, 16 5 mm, 47 5%, 21 or 8%, 19 or an increase in sagittal angulation by more than 15° between flexion and extension.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The spinal canal was increased to 2-to 6.8-fold (mean 4.2 fold) of the pre-operative size. [26] Although the results of microscopic discectomy using tubular retractor have been found to be safe and effective, [27] there is no report of bilateral decompression using microscopic technique to the best of our knowledge.…”
Section: Other Minimally Invasive Technique For Lcsmentioning
confidence: 99%